Feasibility Study of Plumutan Village, Semarang Regency as A Tourism Village: Social, Economic, and Environmental Perspectives - Rachmawati, Meida; Susano, Adhi (Universitas Boyolali, 2025)
Based on social, economic, and environmental factors, this study attempts to investigate Plumutan Village in Semarang Regency's viability as a tourist destination. The study employs a qualitative methodology, gathering data via documentation studies, interviews, and observation. The findings indicate that Plumutan Village has significant potential as a tourism village with advantages in natural beauty, traditional cultural diversity, and distinctive agricultural products. From a social perspective, local communities show a high level of acceptance towards the idea of a tourism village. Economic diversification brought about by the growth of a tourism town can raise local incomes. Environmentally speaking, this community boasts a distinctive ecosystem that can serve as a draw while preserving conservation elements. However, the establishment of suitable marketing tactics, community capacity building, and supporting infrastructure all require improvement. The growth of a tourist community in Plumutan must consider the balance between social, economic, and environmental aspects to realize sustainable tourism development.